Structure and mechanical stresses in TaSi₂/Si multilayer - Devizenko, A.Yu.; Kopylets, I.A.; Kondratenko, V.V.; Pershyn, Y.P.; Devizenko, I.Y.; Zubarev, E.N.; Savitskiy, B.A. (Functional Materials, 2018)
The structure, construction and mechanical stresses of the TaSi₂/Si multilayer manufactured by magnetron sputtering on the heated substrates were studied in the initial state and after thermal annealing. Deposition of multilayers is accompanied by formation of compressive mechanical stress. Reduction of mechanical stresses in the multilayers by increasing of the substrate temperature and after thermal annealing was observed. The thickness of the multilayers and the annealing temperature at which ones separated from the substrate were shown. Thermal annealing is accompanied by changes of the multilayer construction and structure of layers. The deposition of depth graded multilayers with layer thickness distribution according to the Fresnel zone plate law has been performed.